WEBSITE MAKING FOUNDATION AL-HUSNA USING MACROMEDIA DREAMWEAVER 4.0 - Eka Febriyanti; Don Elsyafitra., SKom. (Jurnal Sistem Informasi, 2005)
Website is one of the means to publish a firm or individual who has information to beknown by the wider community, especially users of internet service. At this writing willdiscuss ways in making website.The method used in this writing is to use Macromedia Dreamweaver 4.0 on Windows1998 and Internet Explorer as your browser Exploler 5. Reasons for using MacromediaDreamweaver 4.0 is to be able to design a website according to the author wishes.A good website is a website that can attract the attention of internet users, so they areinterested in opening a website and view the information contained in the internet.